Leadership in Action : Issues and Observations--The Full Nelson--Leadership Lessons from a British Naval Hero - Hurst, David (Center for Creative Leadership, 2007)
A testament to the power of this vision is the extended celebration that took place in Britain in 2005 commemorating the life and heroic death of vice admiral Lord Horatio Nelson.